2017
DOI: 10.1186/s40348-017-0076-8
|View full text |Cite
|
Sign up to set email alerts
|

The BPD trio? Interaction of dysregulated PDGF, VEGF, and TGF signaling in neonatal chronic lung disease

Abstract: The development of neonatal chronic lung disease (nCLD), i.e., bronchopulmonary dysplasia (BPD) in preterm infants, significantly determines long-term outcome in this patient population. Risk factors include mechanical ventilation and oxygen toxicity impacting on the immature lung resulting in impaired alveolarization and vascularization. Disease development is characterized by inflammation, extracellular matrix remodeling, and apoptosis, closely intertwined with the dysregulation of growth factor signaling. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 98 publications
1
23
0
Order By: Relevance
“…However, in line with our previous observations from the plasma proteome, functional analysis also suggested involvement of blood cells, blood platelets, and the fibronectin matrix (31), as well as proteins related to endothelial cell, epithelial cell, fibroblast, and neuronal function. Furthermore, our proteomic analysis not only confirmed known neonatal lung injury pathways, such as the extensively studied vascular endothelial growth factor (32,33) and IL-6 (34-36) signaling pathways, but also identified an entirely novel association with three closely related RXR-mediated nuclear receptor families: LXR/RXR, FXR/RXR, and PPARa/RXRa. Each of the nuclear receptors forms a heterodimer with RXR, and can be activated with agonists against either LXR/FXR/PPARa or RXR during oxidative stress (37,38) or under conditions of energy deprivation (39), resulting in activation of target genes involved in lipogenesis and inflammation.…”
Section: Discussionsupporting
confidence: 63%
“…However, in line with our previous observations from the plasma proteome, functional analysis also suggested involvement of blood cells, blood platelets, and the fibronectin matrix (31), as well as proteins related to endothelial cell, epithelial cell, fibroblast, and neuronal function. Furthermore, our proteomic analysis not only confirmed known neonatal lung injury pathways, such as the extensively studied vascular endothelial growth factor (32,33) and IL-6 (34-36) signaling pathways, but also identified an entirely novel association with three closely related RXR-mediated nuclear receptor families: LXR/RXR, FXR/RXR, and PPARa/RXRa. Each of the nuclear receptors forms a heterodimer with RXR, and can be activated with agonists against either LXR/FXR/PPARa or RXR during oxidative stress (37,38) or under conditions of energy deprivation (39), resulting in activation of target genes involved in lipogenesis and inflammation.…”
Section: Discussionsupporting
confidence: 63%
“…Periostin and TGF-β are known to play a critical role in the proliferation of lung broblasts (9). Furthermore, many studies in different animal models of BPD con rm elevated TGF-β expression levels and activation of its associated pathways as an important part of lung disease pathophysiology (22,26,27). Also, we previously reported that serum TGF-β levels were upregulated in BPD patients (28).…”
Section: Discussionmentioning
confidence: 88%
“…In recent studies, it has been demonstrated that platelet-derived growth factor (PDGF), serving as a vital regulator of alveolar septation, VEGF serving as a vital regulator of pulmonary vascular development, and transforming growth factor (TGF), which affects the apoptosis, matrix remodeling, inflammatory process of pulmonary development play an important part in the pathogenesis of BPD. 29 Studies have consistently demonstrated that plateletrich plasma is also rich in the above-mentioned growth factors, such as PDGF, TGF, and VEGF, and have large effect on the formation of BPD. 30 Moreover, platelets also have important roles in the proinflammatory process.…”
Section: Discussionmentioning
confidence: 99%